Techno-Economic Assessment of the Furnace-Type Lumber Dryer Technology in the Philippines - Magsanoc, Lolinda M. (1991)
The Project covers the assessment of the technical and economic aspects of the furnace-type lumber dryer technology in Regions II and III, Philippines. These regions are located in the northern part of the Philippines where the furniture and woodcraft industry are concentrated. Seven dryers were subjected for assessment for possible damages through time. These include a 1,500 bd. ft. (3.54 cu.m), five (5) 10,000 bd.ft. (23.58 cu.m) and a 12,000 bd.ft.(28.30 cu.m) capacity dryers. Of the five 10,000 bd. ft. (23.58 cu.m) capacity dryers, one was constructed in 1982, two in 1989 and the other two in 1990. The 1,500 bd. ft. (3.54 cu.m) and 12,000 bd. ft.(28.30 cu.m) capacity dryers were constructed in 1982 and 1990, respectively. A major damage was observed on the flue pipe of the 1982 - 10,000 bd.ft. (23.58 cu.m) dryer. However, a temporary measure was adopted hence it is still in operation. The newly constructed dryers on the other hand have slight damages on the furnace and flue pipe which was attributed to improper firing and carelessness in operation. The economic feasibility study shows that the payback period is within three or four years of operation for all kiln capacities. Managers however revealed that within a year of operation or at about 10 loadings of a 10,000 bd. ft.(23.58 cu.m) dryer, they have recovered the cost of establishment.